Amotekun and the Fight against Crime: The Role of Technology in Community Policing in Southwest Nigeria - Awotayo, Olagoke Oluwafemi; Adeosun, Adewale; Okunola, Samson Kunle; Omitola, Bolaji (Kashere Journal of Politics and International Relations, 2025)
This paper looks at two promising strategies to improve public safety in Nigeria: giving state governments more control over gun regulation and using modern technology to strengthen community policing. It focuses on the Amotekun Corps a regional security outfit in the Southwest as a practical example of how these ideas can work on the ground. The core argument is that when states are allowed to manage firearm policies under federal guidance, they can respond more effectively to local security issues like armed robbery and kidnapping. Amotekun’s efforts show how technology such as data analytics, mobile communication tools, and surveillance systems can boost crime prevention and make operations more efficient. The paper proposes a hybrid model that blends innovation with localized governance. This approach could help build safer communities, increase public trust in law enforcement, and ensure greater accountability. Of course, there are risks like potential misuse of firearms or weak oversight but the study stresses the importance of strong regulations to keep things in check. In the end, it advocates for a security system that’s flexible, tech-savvy, and tailored to the unique needs of each region one that can adapt to Nigeria’s evolving safety challenges and offers a more stable future.